2018
DOI: 10.1111/nmo.13324
|View full text |Cite
|
Sign up to set email alerts
|

Cross cultural comparison of constipation profiles at tertiary care centers between India and USA

Abstract: Indian patients with CC have more frequent and softer bowel movements compared to those in the USA suggesting significant differences in perception of CC in different geographic and cultural settings. QOL and economic impact related to constipation varies with geographic/cultural setting irrespective of other clinical and psychosomatic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The epidemiological survey showed that the incidence rate of constipation was 27%, and the prevalence rate of males and females was about 1 : 1.5 (Tian et al, 2019;Guo et al, 2002). At present, the studies have found that people in economically underdeveloped areas and those with low education levels are more likely to have constipation (Ebling et al, 2014), which is related to race and region (Roque & Bouras, 2015;Chu et al, 2014;Singh et al, 2018). Chronic constipation is closely related to multiple system diseases, such as cardiovascular and frequency of defecation, soften the stool and facilitate excretion (Escribano et al, 2018;Yu et al, 2017;Barichella et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiological survey showed that the incidence rate of constipation was 27%, and the prevalence rate of males and females was about 1 : 1.5 (Tian et al, 2019;Guo et al, 2002). At present, the studies have found that people in economically underdeveloped areas and those with low education levels are more likely to have constipation (Ebling et al, 2014), which is related to race and region (Roque & Bouras, 2015;Chu et al, 2014;Singh et al, 2018). Chronic constipation is closely related to multiple system diseases, such as cardiovascular and frequency of defecation, soften the stool and facilitate excretion (Escribano et al, 2018;Yu et al, 2017;Barichella et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The details were listed in Table 7. cerebrovascular diseases, colorectal tumors, and so on (Singh et al, 2018;Dehghani et al, 2013).…”
Section: Changes Of Constipation In Two Groupsmentioning
confidence: 99%
“…The previous study showed that its prevalence has been steadily increasing from 11% to 18% in communities [1]. Based on the literature [2], the occurrence of constipation has also been shown to vary according to race and the regions that sufferers live in. Although the symptoms of constipation are generally harmless, they are sometimes warn� ing signs of more serious conditions including colorectal cancer, cardiocerebrovascular and kidney disease [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, self‐perceived constipation is expected to be commoner in Asia. In a comparative study of tertiary care patients with chronic constipation from India and USA, Indian patients had more frequent stools (median 5 vs. 3/week), fewer hard stools (Bristol 1 and 2, 48% vs. 65.5%), lower constipation severity, lower depression scores and better quality of life than patients from the USA 5 …”
mentioning
confidence: 99%
“…3/week), fewer hard stools (Bristol 1 and 2, 48% vs. 65.5%), lower constipation severity, lower depression scores and better quality of life than patients from the USA. 5 What could be the reasons for these differences? Although both nations recruited secondary care patients, there could be recruitment bias as strict and restricted referral system may lead to selection of patients with more severe illness in the West than in Asia…”
mentioning
confidence: 99%